Quality of Research for Development in the CGIAR Context - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
The ISPC is facilitating System-wide agreement on the nature and assessment of quality of research for development (QoR4D), and a working group on QoR4D was established in 2016 under ISPC chairmanship. The consultative process led to a consensus that QoR4D in the CGIAR context should be viewed as an integrated whole of four key elements: relevance, scientific credibility, legitimacy and effectiveness that could be the basis for a common frame of reference across the System.